Churchill Sustainability Planning Framework (CSPF) - Distasio, Jino; Dudley, Michael; Moradzadeh, Fereshteh (Institute of Urban Studies, 2015)
Report: Xiii, 159 pp.; ill., digital file. e current report is the Churchill Sustainability Planning Framework (CSPF) which sets out the Vision, Values and Priorities for making Churchill a more sustainable community, and provides a “toolkit” for moving these priorities into action. It addresses the environmental, social and economic aspects of sustainability, and makes speciD c recommendations for the updated Community Plans and Urban Design. In order to direct town of Churchill’s resources toward achieving the community’s vision, the current framework is oriented to six interrelated priority areas which may be summarized as: Food Security, Economic Development, Youth Education, Training and Recreation, Waste Management, Housing, and Built Environment. OmniTrax inc.